Ceramic membranes : new opportunities and practical applications - Gitis, Vitaly (Wiley-VCH, 2016)
An essential textbook in the growing field of ceramic membranes, covering an introduction, a concise treatment of the fundamentals of membrane separation, an overview of ceramic membrane characterisation techniques, industrial applications and the economics.
Keywords: Membranes (Technology); Ceramic materials.; Gas separation membranes.; elektronické knihy; electronic books